Strategies to enhance clinical teaching and learning in undergraduate nursing education: A scoping review - Kafui A. Hobenu; Anthonio O. Adefuye; Florence Naab; Champion N. Nyoni (PLoS ONE, 2025)
Background Nursing education comprises theory and practice as two complementary parts. Nursing is a practice-based profession, and students are expected to be practically competent in rendering quality care to the deserving population. Clinical training allows nursing students to gain the practical skills required in the nursing profession. In addition to the practical skills, clinical education helps students to learn skills such as problem-solving, decision-making and critical thinking. However, evidence exists that students cannot acquire clinical competence due to multiple factors. These factors are related to students, the clinical environment, and the nurse/faculty. There is a need to identify strategies to enhance clinical teaching and learning in undergraduate nursing education. Therefore, this scoping review aims to identify evidence-based strategies to support clinical teaching and learning in undergraduate nursing education. Methods A scoping review method underpinned by Peters et al. (2020) framework was employed. A search string developed from the title of the review was used to search online databases to identify peer-reviewed articles published between January 2011 and September 2023. Results Forty studies were included in the review, most originating from the United States. Seven themes were identified: scaffolding the curriculum, transformative teaching and learning approaches, integrating simulation-based education, dedicated education units for clinical placement, applying technology in clinical education, developing interprofessional teamwork and collaboration, and integrating inter-country clinical experience. Conclusion The current scoping review has unveiled strategies relevant to nursing students’ clinical teaching and learning. These strategies could guide curriculum developers, programme organisers, nursing teachers, nursing students, and clinical instructors at clinical learning sites in restructuring clinical teaching and learning in undergraduate nursing education to improve clinical education outcomes.